Representasi Bahasa dalam Film Dokumenter “Dilema Bahasa: Nasib Bahasa Jawa Hari Ini” - Shelly Aulia; M. Fauzi Djamal (UNISBA Press, 2023)
Abstract. Language is the distinguishing feature of humans compared to other creatures. Language is an important system of communication in culture. Language is involved in every aspect of culture. In this research, it will discuss a documentary film on Watchdoc Documentary channel, documentary film is an event that can be watched in recordings. Representation of Language in Documentary Film Dilema Bahasa: Fate of Javanese Language Today, the study analyzed the form of symbols, icons, and indices from the film. Semiotic theory investigates various signs in various aspects of life. Symbols of language are among the most important. Charles Sanders Pierce's theory used for this research is able to divide the classification based on its interpreter. This research aims to examine the representation of language in Documentary Film Dilema Bahasa: Fate of Javanese Language Today through Charles Sanders Pierce's Semiotic Analysis Unit. The method used in this research is qualitative with a semiotic descriptive approach. Observations or observations were made by directly observing each scene, dialogue, and gesture in the documentary film